Prediction of quasi-static mechanical properties of flexible porous metal rubber structures in ultra-wide temperature range - Mingqiang Zhang; Yalin Ding; Guoqin Yuan; Hongwen Zhang; Lin Sun; Jianjun Sun; Yaobin Li (Composites Part C: Open Access)
Metal rubber, which has the advantages of low density, strong environmental adaptability, and excellent design flexibility, is widely applied in manufacturing industries such as the aerospace, shipping, and automotive industries. Based on the research object of flexible porous metal rubber (FPMR) structures made of high-temperature elastic alloys, this study established a constitutive model for the quasi-static mechanical properties of FPMR structure under ultra-wide temperature range conditions. Firstly, the forming mechanism and the influencing factors of the static stiffness properties of the FPMR micro-structure were analyzed. Then, the theoretical model of the FPMR micro-element spring was established by applying the cylindrical spiral compression spring stiffness theory, and the theoretical model was corrected based on the large deformation theory and numerical analysis methods. A comparative analysis was carried out through the corrected theoretical model and the test results of different test samples. And the results show that the corrected theoretical model can comprehensively reflect the nonlinear quasi-static stiffness characteristics of the FPMR structure in an ultra-wide temperature range. More importantly, by comparison with the prediction models proposed by other scholars, it is proved that the model proposed in this paper has higher prediction accuracy and the goodness of fit R2 is closer to 1, which provides a theoretical basis for the application of metal rubber in flexible support structures under ultra-high temperature environments.